The claustrum’s proposed role in consciousness is supported by the effect and target localization of Salvia divinorum - Stiefel, Klaus M.; Merrifield, Alistair; Holcombe, Alex O. (Frontiers in Integrative Neuroscience, 2014)
This article brings together three findings and ideas relevant for the understanding of human consciousness: (I) Crick’s and Koch’s theory that the claustrum is a “conductor of consciousness” crucial for subjective conscious experience. (II) Subjective reports of the consciousness-altering effects the plant Salvia divinorum, whose primary active ingredient is salvinorin A, a κ-opioid receptor agonist. (III) The high density of κ-opioid receptors in the claustrum. Fact III suggests that the consciousness-altering effects of S. divinorum/salvinorin A (II) are due to a κ-opioid receptor mediated inhibition of primarily the claustrum and, additionally, the deep layers of the cortex, mainly in prefrontal areas. Consistent with Crick and Koch’s theory that the claustrum plays a key role in consciousness (I), the subjective effects of S. divinorum indicate that salvia disrupts certain facets of consciousness much more than the largely serotonergic hallucinogen lysergic acid diethylamide (LSD). Based on this data and on the relevant literature, we suggest that the claustrum does indeed serve as a conductor for certain aspects of higher-order integration of brain activity, while integration of auditory and visual signals relies more on coordination by other areas including parietal cortex and the pulvinar.